Inherently chiral electrodes: the tool for chiral voltammetry. Issue 3 (16th March 2015) - Arnaboldi, Serena; Benincori, Tiziana; Cirilli, Roberto; Kutner, Włodzimierz; Magni, Mirko; Mussini, Patrizia Romana; Noworyta, Krzysztof; Sannicolò, Francesco
<x xml:space="preserve">Abstract</x> Artificial inherently chiral electrode surfaces perform clear enantiodiscrimination and enantiomeric ratio quantification, opening the way to chiral voltammetry.